2023
DOI: 10.5507/bp.2022.033
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of three alternative prophylactic antibiotics during cardiac surgery with extracorporeal circulation

Abstract: The aim of this pharmacokinetic study was to describe and quantify population pharmacokinetics of three antibiotics, cefazolin, ampicillin, and ciprofloxacin, used as antibacterial prophylaxis during cardiovascular surgery with the use of extracorporeal circulation (ECC). Methods. Adult patients undergoing cardiac surgery with ECC were enrolled to this prospective, pharmacokinetic study. An intravenous bolus of 2 g of ampicillin, 2 g of cefazolin or 400 mg of ciprofloxacin was administered 60-30 min before sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…A population pharmacokinetic study by Asada et al revealed decreased cefazolin clearance and an increased volume of distribution during CPB with insufficient probability of target attainment (PTA) for pathogens with MIC > 8 mg/L [ 16 ], which is fortunately not a very common situation in cardiothoracic surgery practice. Cefazolin pharmacokinetics in patients receiving MiECC support was also preliminary explored [ 17 ]; however, differences in the influence of cefazolin pharmacokinetics between ECC and MiECC—if they exist—have not yet been studied using a direct comparison or a comparison with an internal control.…”
Section: Introductionmentioning
confidence: 99%
“…A population pharmacokinetic study by Asada et al revealed decreased cefazolin clearance and an increased volume of distribution during CPB with insufficient probability of target attainment (PTA) for pathogens with MIC > 8 mg/L [ 16 ], which is fortunately not a very common situation in cardiothoracic surgery practice. Cefazolin pharmacokinetics in patients receiving MiECC support was also preliminary explored [ 17 ]; however, differences in the influence of cefazolin pharmacokinetics between ECC and MiECC—if they exist—have not yet been studied using a direct comparison or a comparison with an internal control.…”
Section: Introductionmentioning
confidence: 99%